Evaluation of pulping therapy in deciduous teeth using chlorhephenicol tetracycline and Zinc oxide - Gisele Fernandes DIAS; Juciane TRAMONTIN; Priscila Pelexate dos SANTOS; Fernando ROSSI; Mylena RIGONI (Faculdade São Leopoldo Mandic, 2021)
ABSTRACT The technique using CTZ paste (chloramphenicol, tetracycline, and zinc oxide-eugenol) in the endodontic treatment of deciduous teeth is easy to perform and requires a single session, which is an advantage with child patients. The inexistence of clinical protocols with the use of CTZ and the multifactorial endodontic repair process in deciduous teeth evidence the need for research on the subject. This study aimed to suggest a clinical protocol model for the systematization and standardization of the endodontic treatment of deciduous teeth using CTZ paste. In the case report presented, after pulp therapy, clinical-radiographical follow-up was conducted after 30, 60, 90 and 180 days. It was concluded that using CTZ paste is a simple, viable, and satisfactory alternative. Future clinical studies are needed regarding CTZ use in child clinic with strong scientific evidence.